The influence of political pressure groups on the stability of international environmental agreements - Achim Hagen; Juan Carlos Altamirano Cabrera; Hans-Peter Weikard (University of Oldenburg, Department of Economics, 2016)
This paper examines the effects of political pressure groups (lobbies) on the emissions abatement decisions of countries and on the stability of international environmental agreements. We consider two types of lobbies, industry and environmentalists. We determine the influence of lobby-groups on the abatement decisions of countries. This influence affects members of an international environmental agreement as well as outsiders. However, in the case of agreement members, the effects of lobbying are not restricted to the lobby's host-country but spill over to other member countries and have ambiguous effects on the agreement stability.
Keywords: C72; D72; D78; H41; Q28; Q54; 330; interest groups; coalition theory; environmental policy making; international environmental agreements